-2х+2х^2+3х-12=-х^2-2х-6х
- 2х (1-х) + 3 (х-4) = -х (х+2) – 6х

-2х – 2х2 + 3х – 12=х2 + 2х – 6х

2х2 + 9х + 12 =0

Д = в2 – 4ас

Д = 92 – 4*2*12

Д=81-96

Д = -15

Так как дискриминант меньше нуля, то уравнение не имеет кореней.

Ответы и объяснения

2014-04-12T12:43:48+00:00
-2x+2x^2+3x-12=2x^2+x-12
- 2х (1-х) + 3 (х-4) = -х (х+2) – 6х

-2х – 2х2 + 3х – 12=х2 + 2х – 6х

2х2 + 9х + 12 =0

Д = в2 – 4ас

Д = 92 – 4*2*12

Д=81-96

Д = -15

Так как дискриминант меньше нуля, то уравнение не имеет кореней.
по моему так. но я не уверена.